Treating learned helplessness in the elderly dementia patient preliminary inquiry - Flannery, Raymond B. Jr.
Learned helplessness is the psychological state that results when an individual who is unable to exercise reasonable mastery in one situation incorrectly assumes that he or she is then unable to exercise reasonable control in other situations as well. This may complicate the delivery of health interventions since the individual with learned helplessness may assume that no care provider or treatment intervention can be of assistance. Elderly patients with Alzheimer's disease and other dementias are not immune to this stance of learned helplessness. This paper presents one possible psychosocial rehabilitation approach, the Project SMART (Stress Management and Relaxation Training) program, to the problem of learned helplessness. Based on the skills of adaptive stress-resistant problem solvers, Project SMART can be adapted to the needs of the elderly demented. The clinical and research implications are discussed.
Includes bibliographic references.
Keywords: Alzheimer's disease; Dementia -- Patients -- Care